The Use of Process Approach in Teaching Writing Recount Text to the 10th Graders (RETAIN, 2017)
The Use of Process Approach in Teaching Writing Recount Text to the 10th Graders Riza Faisma Umim English Education, Language and Art Faculty, State University Surabaya rizafaisma@yahoo.com Esti Kurniasih, S.Pd, M.Pd English Education Department, Faculty of Language and Art, State University of Surabaya Estikurniasih@unesa.ac.id Abstrak Banyak siswa yang mempunyai kesulitan dalam menulis sebuah karya tulis karena guru hanya menjelaskan teori. Salah satu pendekatan yang dapat digunakan guru dalam mengajar menulis adalah pendekatan proses (process approach) karena peran guru tidak hanya menjelaskan teori tetapi juga membimbing para siswa untuk menulis. Oleh karena itu, penilitian ini ditujukan untuk menginvestigasi bagaimana guru dapat membantu siswa menulis sebuah karya tulis dengan menerapkan process approach. Penelitian ini menggunakan penelitian deskriptif untuk mendeskripsikan penerapan process approach, karya tulis siswa, dan respon siswa terhadap penerapan process approach. Penelitian ini dilakukan di salah satu SMA di Gresik. Subjek dari penelitian ini adalah 26 siswa dan satu guru bahasa inggris. penelitian ini menggunakan observasi, karya tulis siswa, dan kuesioner untuk mengumpulkan data. Instumen penelitian yang digunakan adalah observation checklist, catatan, karya tulis murid dan kuesioner. Setelah itu, informasi dari observation checklist, catatan, karya tulis murid, dan kuesioner akan dianalisis. Penelitian ini menunjukkan bahwa guru menerapkan process approach dalam tiga pertemuan yang mencakup lima langkah; pre-writing, drafting, revising, editing, and publishing. Dengan menerapkan process approach, para siswa dapat menulis sebuah karya tulis yang baik. Para siswa juga mempunyai respon yang positif terhadap penerapan process approach dalam pengajaran menulis. Kata Kunci : Menulis, Process Approach, Recount Text Abstract Most of the students have difficulties in writing a composition because the teacher only explains the theory. One of the approaches that can be used by the teacher in teaching writing is process approach because the teacher not only explains the theory but also guides the students to write a composition. Therefore, the researcher tries to investigate how the teacher can help students in writing a composition by using process approach. This research used descriptive qualitative research design to describe the implementation of process approach, the students’ composition and the students’ responses toward the use of process approach. This study was conducted in one of the senior high schools in Gresik. The subjects of this study were 26 students and an English teacher. The researcher used observation, students’ composition and questionnaire to collect the data. The research instruments were observation checklist, field note, the students’ composition and questionnaire. After getting the data, the researcher analyzed the data by describing the information from observation checklist, field note, students’ composition, and questionnaire. The research showed that the teacher implemented process approach in three meeting that covers five steps; pre-writing, drafting, revising, editing, and publishing. By implementing process approach, the students can write good composition. The students also have positive response toward the use of process approach. Keyword: Writing, Process Approach, Recount Text